Impact of Intraoperative Magnetic Resonance Imaging (i-MRI) on Surgeon Decision Making and Clinical Outcomes in Cranial Tumor Surgery - Bunyaratavej, Krishnapundha; Siwanuwatn, Rungsak; Tuchinda, Lawan; Wangsawatwong, Piyanat (Asian Journal of Neurosurgery, 2022)
Background Although intraoperative magnetic resonance imaging (iMRI) has an established role in guiding intraoperative extent of resection (EOR) in cranial tumor surgery, the details of how iMRI data are used by the surgeon in the real-time decision-making process is lacking.Materials and Methods The authors retrospectively reviewed 40 consecutive patients who underwent cranial tumor resection with the guidance of iMRI. The tumor volumes were measured by volumetric software. Intraoperative and postoperative EOR were calculated and compared. Surgeon preoperative EOR intention, intraoperative EOR assessment, and how iMRI data impacted surgeon decisions were analyzed.Results The pathology consisted of 29 gliomas, 8 pituitary tumors, and 3 other tumors. Preoperative surgeon intention called for gross total resection (GTR) in 28 (70%) cases. After resection and before iMRI scanning, GTR was 20 (50.0%) cases based on the surgeon's perception. After iMRI scanning, the results helped identify 19 (47.5%) cases with unexpected results consisting of 5 (12.5%) with unexpected locations of residual tumors and 14 (35%) with unexpected EOR. Additional resection was performed in 24 (60%) cases after iMRI review, including 6 (15%) cases with expected iMRI results. Among 34 cases with postoperative MRI results, iMRI helped improve EOR in 12 (35.3%) cases.Conclusion In cranial tumor surgery, the surgeon's preoperative and intraoperative assessment is frequently imprecise. iMRI data serve several purposes, including identifying the presence of residual tumors, providing residual tumor locations, giving spatial relation data of the tumor with nearby eloquent structures, and updating the neuro-navigation system for the final stage of tumor resection.
Keywords: cranial tumor; extent of resection; glioma; gross total resection; intraoperative MRI